Computational study of active compounds of Citrullus lanatus Linn peel extract as potential antidiabetics - Sari, Shinta Dewi Permata; Budiman, Muhamad Arif; Ningsih, Sri Suciati (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Diabetes mellitus (DM) is one of the metabolic diseases that have emerged as a global health problem. Type 2 diabetes mellitus (T2DM), which affect 90-95% of DM, is caused by reduced insulin sensitivity and insulin resistance in peripheral tissues. Oral antidiabetics have resulted side effects, prompting an investigation for a natural-based antidiabetic agent as an alternative treatment. Using network pharmacology, we investigated the mechanism of phytochemical substances of Citrulus lanatus Linn. peel extract and their interactions with target proteins in the DM pathogenesis pathway. Cytoscape 3.6.1 software has created a network of extract compound-protein targets. Investigation of protein interaction, target gene function enrichment, and signal pathway performed via DAVID, STRING database, and the KEGG pathway database. The computational study identified 90 target proteins associated with T2DM based on protein-protein interactions. In addition, Cytoscape analysis and DAVID enrichment revealed the network of extract compound's target and generated proteins such as INS, TNF-α, IL-6, and AKT2. The KEGG pathway analysis presented the crucial role of insulin resistance and AGE-RAGE signaling pathways. This pathway correlated with lower glucose activity in obesity and hyperglycemia. It indicates that the active constituents of C. lanatus Linn peel extract can lower blood sugar levels by interacting with selected proteins. This study's findings will be carried out in further research of in vitro trials.